(untitled) (Research, Society and Development, 2022)
Health education is not static, but has undergone constant changes over the years, adjusting to new challenges and seeking to facilitate learning for new generations. During the improvement trajectory, new methodologies are incorporated. We recently went through the biggest pandemic of the century, Covid-19, which accelerated the processes and advances that unite education and technology. Problem-based learning, communication skills training, and simulation-based learning entered curricula. The objective of the study was to introduce a new method of learning in infectology, through gamification. In this project, a mobile application with gamification components was developed as an auxiliary teaching tool in infectious and parasitic diseases for undergraduate medical students. The residency test questions were selected and were distributed in: Sexually transmitted infections (N=30), General Infectology (N=101), Antimicrobials (N=33) and HIV/AIDS (N=30). During access, students answer a battery of 10 objective questions, where correct answers and speed of response to classification parameters (ranking) are measured. At the end, the correct answers are presented to the candidates. The game was registered by the National Institute of Industrial Property, with the title InfeQ (IOS AND ANDROID). It is concluded that the application called InfeQ® has usability for the demand for knowledge in the area of ​​infectology with a focus on medical residency tests and public tender.